Enhancing Students' Learning Interest Through Teachers' Professional Competence - Tri Andri Magfira; Azizah Azizah (Horizon of Primary Education, 2025)
This research aims to determine the role of teachers' professional competencies in stimulating students' interest in learning. This research used a descriptive qualitative method. The study population was teachers and students in grades 4, 5, and 6 of SD Inpres 3 Kasimbar. A proportional random sampling technique was used to determine 15% of the total population as the sample consisted of 3 teachers and 24 students. Data collection techniques were observation, interviews, documentation, and questionnaires. The data analysis technique used descriptive qualitative. The results showed that the teachers' professional competence in SD Inpres 3 Kasimbar is good, and they carry out the learning process well. This situation affects students' interest in learning. The results also indicated that the teachers' professional competence in elementary school is excellent, and students at SD Inpres 3 Kasimbar have a very high learning interest. Several factors support the teachers' professional competencies include students' condition, school facilities, and infrastructure.